Memrise and the Pursuit of Proficiency: A Phenomenological Study on Students' Experiences and Independent Learning Strategies for TOEFL Vocabulary - Dimitria Rahayu; Awwalia Fitrotin Izza (Universitas Islam Negeri Palopo, 2025)
This phenomenological study investigated the lived vocabulary learning experiences of seven high-stakes TOEFL candidates (N=7) who used the Memrise Spaced Repetition System (SRS) app. Through Interpretive Phenomenological Analysis (IPA), the study confirmed that while gamified features offer strong structural support for consistency and efficient recognition-based memorization, the learning process is structurally incomplete within the app. The central finding is a persistent recognition–production gap, meaning vocabulary learned passively in the app fails to transfer directly to the active, contextual production required by the TOEFL exam. Success, therefore, hinged on learners' active, metacognitive effort and the implementation of external compensatory strategies, such as dedicated sentence journaling and custom course creation. These findings suggest the motivational benefits of gamification are conditional and can risk a focus on volume over learning quality. Results have significant implications for Mobile Assisted Language Learning (MALL) design, calling for integrated features that foster contextual application. Ultimately, this work benefits app designers, language teachers, and autonomous learners by specifying the structural and metacognitive requirements for effective vocabulary learning via SRS applications.